Deus ex Machina Boss: Managerial Powers in Workplaces Governed by Algorithms and Artificial Intelligence - Aloisi, Antonio (Nomos, 2023)
Is the existing legal framework capable of responding to the phenomenon of so-called "algorithmic bosses"? What will happen if technology ultimately disrupts the traditional boundaries of managerial powers that are, in principle, considered lawful? This study aims to examine the extent to which digital automation has led to the expansion of the organizational, supervisory, and disciplinary privileges already available to employers and managerial staff. Using plain language, the study is structured into four sections. Section 2 explores the purposes of the employment relationship and clarifies the notion of the authoritative position held by employers. Section 3 presents the most prevalent artificial intelligence and algorithmic technologies currently entering the workplace; it is argued in this section that, despite their diverse applications, a common denominator lies in their capacity to record and process information that may be used to support managerial staff in making executive decisions. Section 4 identifies the risks that arise when managerial privileges are expanded through the adoption of automated decision-making, as mandatory legal provisions, procedural safeguards, and compensatory mechanisms stemming from collective bargaining are subject to continuous pressure. Adopting a multidimensional approach, this section proposes remedial measures derived from data protection law and anti-discrimination regulations, which—when combined with labor law—could serve to rein in the power of algorithmic bosses. Section 5 offers some concluding observations.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 8 - Trabajo decente y crecimiento económico; ODS 16 - Paz, justicia e instituciones sólidas